Sifat Pembakaran Briket Bioarang Berbahan Dasar Campuran Arang Kotoran Kambing, Tempurung Saboak dan Sekam Padi - Alokafani, Febi; Dami Dato, Twenfosel O.; Maranatha, Grace; Riwu, Agustinus R. (Animal Agricultura, 2025)
This study aims to determine the effect of goat dung charcoal mixture of saboak shell and rice husk on the combustion properties of biocharcoal briquettes. The method used is a completely randomized design (CRD) with 4 treatments and 4 replicates. The treatments were P1 = 25% goat dung charcoal + 75% saboak shell, P2 = 25% goat dung charcoal + 50% saboak shell + 25% rice husk, P3 = 25% goat dung charcoal + 25% saboak shell + 50% rice husk and P4 = 25% goat dung charcoal + 75% rice husk. The variables studied included combustion temperature, combustion rate, combustion resistance, combustion and smoke color, and the ability to boil water. The results of the variance showed that the treatment had a significant effect (P < 0.05) on the combustion temperature, combustion rate, and a very significant effect (P < 0.01) on the ability to boil water, but not significant (P>0.05) on combustion resistance, color and smoke. The average values obtained are combustion temperature 270.2 ⁰C; combustion rate 2.40 g/min; combustion resistance 218.8 minutes; combustion color 3.50; combustion smoke 3.50; ability to boil water 11.68 minutes. It was concluded that biochar briquettes made from a mixture of goat dung charcoal, saboak shell and rice husk with an increasing proportion of rice husk, produced briquettes with combustion quality: combustion temperature, and water boiling ability decreased, but combustion resistance, combustion rate, color and smoke tended to be the same.